Temperature effect on the characteristics and lifetime of semiconductor detectors - Vasiliyev, G.P.; Kosinov, A.V.; Kulibaba, V.I.; Maslov, N.I.; Naumov, S.V.; Ovchinnik, V.D.; Yalovenko, V.I. (Вопросы атомной науки и техники, 2006)
The paper reports the results from studies into the effect of temperature on the performance characteristics of planar silicon detectors designed and manufactured at the NSC KIPT. A variety of techniques are demonstrated for measuring the temperature effect on various static and spectral characteristics of single-channel planar detectors. The relationship between the static characteristics of detectors and their long-term stability and lifetime is considered.